Geometric structure and properties of linear time invariant multivariable systems in the controller canonical form - Kazantzidou, C.; Ntogramatzidis, Lorenzo (The Institution of Engineering and Technology, 2017)
In this study, the authors analyse some fundamental structural properties of linear time-invariant multivariable systems in the controller canonical form and present a direct method for the computation of bases and associated friends for output-nulling, input-containing and reachability subspaces in terms of the parameters of the system and the invariant zero structure, both in the non-defective and in the defective case. Using this analysis, it is possible to express the solvability conditions of important control and estimation problems in terms of easily checkable conditions on the system matrices.